A REMARK ON SYMMETRIC β-UNIFORMLY CLOSED ALGEBRA - Karakhanyan, M.I. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2015)
The conjugate space of β-uniformly closed, symmetric algebras of functions on topological spaces are investigated. An application of such spaces in algebras of almost periodic functions is given.